Fluid Secretion of Fallopian Tube Epithelial Cells of Mice (Mus musculus) BALB/C with Pelvic Inflammatory Disease (PID) Infected with Candida albicans Post Therapy with Myrmecodia sp. Jack Extract - Pratisa Delfiera Ajiza; Noor Hujattusnaini; Ayatussa'adah Ayatussa'adah (Universitas Labuhanbatu, 2025)
This study examines the therapeutic potential of Myrmecodia sp. extract in treating Pelvic Inflammatory Disease (PID) induced by Candida albicans in Balb/c mice. The study used a true experimental design with a post-test group. The method involved administering Myrmecodia sp. extract with various concentrations (from 0.4 to 3.2 %) to female Balb/c mice suffering from PID. Observations included clinical indicators of infection, the number of bacterial colonies, and histopathological changes in the epithelial cells of the fallopian tube mucosa. The results showed that Myrmecodia sp. contains flavonoids, tannins, terpenoids, and saponins, which have antimicrobial and anti-inflammatory properties. The mice that were infected with Candida albicans had a lot fewer bacterial colonies after being treated with Myrmecodia sp. extract, but it did not completely get them back to how they were before the infection. The ANOVA test showed that there were important differences between the treatment groups, which shows that Myrmecodia sp. works as an extra treatment for PID. These results confirm the potential of Myrmecodia sp. as an alternative herbal therapy for PID, although further research is needed to improve its effectiveness and understand its mechanism of action.